Good work, Secret Seven - Blyton, Enid; Kay, Bruno (Hodder Children's Books, an imprint of Hachette Chilren's Group, part of Hodder & Stoughton London, 2009)
The Secret Seven are Peter and his sister Janet, Jack, Colin, George, Pam and Barbara. They meet every holiday in the shed at the bottom of Peter and Janet's garden - and solve mysteries, and eat lots of delicious food. But no one can enter the shed without whispering the secret password! There are 15 Secret Seven novels, and a collection of short stories. When a sinister-looking man gets George into trouble with the police, the Secret Seven are outraged. Spying on him, the gang are certain he's bad news. But what exactly is he up to? They need to investigate, and solve the mystery once and for all. Each book features rarely seen bonus Blyton: extra stories, a quiz, additional artwork and insights into Blyton's life and writing process